Linguistic Citizenship as Utopia - Stroud, Christopher (Multilingual Margins: A journal of multilingualism from the periphery, 2017)
major challenge of our time is to build a life of equity in a fragmented world of globalized ethical, economic and ecological meltdown. In this context, language takes on singular importance as the foremost means whereby we may engage ethically with others across encounters of difference. Howevever, there is an important sense in which the crisis of humanity we are experiencing as a crisis of diversity and voice is deeply entwined with a subterranean crisis of language itself. As Giorgio Agamben has pointed out, although language is the foremost realization of our humanity, our current understanding of language distorts rather than elucidates this humanity.